PENGARUH SKEPTISME PROFESIONAL, INDEPENDENSI DAN PENGALAMAN PEMERIKSA PAJAK TERHADAP PENDETEKSIAN KECURANGAN (FRAUD) DENGAN MORALITAS INDIVIDU SEBAGAI VARIABEL MODERASI (STUDI PADA KPP DI KOTA MEDAN) - Lubis, Mutiara Andora; Hani, Syafrida; Sari, Eka Nurmala (Worksheet : Jurnal Akuntansi, 2025)
This study was conducted to examine and analyze the influence of tax auditor skepticism, independence, and experience on Fraud detection with individual morality as a moderating variable. The study used an associative research approach. Data collection techniques included distributing questionnaires. The sampling technique used a quota sampling technique with 49 respondents and path analysis using SEM PLS version 4. Based on the results, it was concluded that Professional Skepticism has a positive and significant effect on Fraud at the Tax Office in Medan City. This means that when companies increase the application of Professional Skepticism, the Good performance will increase Fraud prevention. Independence has a positive and significant effect on Fraud prevention at the Tax Office in Medan City. This means that when companies improve the implementation of good independence, it will increase Fraud prevention. Tax auditor experience has a positive and significant effect on Fraud prevention at the Tax Office in Medan City. This means that when companies improve the implementation of good tax auditor experience, it will increase Fraud prevention. Professional skepticism has a positive and significant effect on Fraud prevention, with individual morality as a moderating variable at the Tax Office in Medan City. Individual morality mediates the effect of independence on Fraud prevention at the Tax Office in Medan City in a positive direction. This means that individual morality strengthens the relationship between independence and Fraud prevention. Individual morality mediates the effect of tax auditor experience on Fraud prevention at the Tax Office in Medan City. This means that individual morality strengthens the relationship between tax auditor experience and Fraud prevention